Negation and nonveridicality in the history of Greek - Chatzopulu, Katerina 1979- (Oxford Oxford University Press USA - OSO, 2019)
This book provides a thorough investigation of the expression of sentential negation in the history of Greek, based on extensive data from major stages of the language. It also provides a new semantic interpretation of Jespersen's cycle that explains the Greek developments and those in other languages.
Cover -- Negation and Nonveridicality in the History of Greek -- Copyright -- Contents -- Series preface -- Preface -- List of abbreviations -- List of figures and tables -- Figures -- Tables -- 1: Introduction -- 1.1 The two-negator system of Greek -- 1.2 Theoretical backgrounds: semantics, syntax, and agreement -- 1.3 Selection of texts and methodology -- 1.4 Periodization -- 1.4.1 Classical Greek (fifth to fourth centuries bc): the Attic dialect -- 1.4.2 Hellenistic and Roman times (third century bc to fourth century ad): Atticism and the Koine -- 1.4.3 Early Medieval Greek (fifth to tenth centuries ad) -- 1.4.4 Late Medieval Greek (eleventh to fifteenth centuries ad) -- 1.4.5 Early Modern Greek (sixteenth to nineteenth centuries ad) -- 1.5 Previous work -- 1.5.1 The Classical scholars -- 1.5.2 More recent contributions within linguistics -- 1.6 Markedness, the Nonveridicality projection, and pragmatic grounding -- 1.7 Roadmap -- 2: The (non)veridicality theory of polarity and negator selection -- 2.1 Negative polarity: precursors and (non)veridicality (Giannakidou 1998) -- 2.2 Polarity phenomena in Standard Modern Greek -- 2.2.1 Negative polarity items -- 2.2.2 The focus particle τ /út/: an instantiation of a negative polarity EVEN -- 2.2.3 (Non)veridicality and mood choice -- 2.2.4 (Non)veridicality and negator choice -- 2.2.4.1 Standard Modern Greek negators -- 2.2.4.2 The distribution of Neg1 and Neg2 in Standard Modern Greek -- 2.3 Crosslinguistic analogies -- 2.4 Beginning the journey: the oldest language relatives and the first attestations -- 2.4.1 Indo-European origins and affinities -- 2.4.2 Homeric Greek negators and traces of the Proto-Indo-European negatives -- 2.4.3 The homotics νή /nε:/ and μά /ma/: remnants of (Proto-)Indo-European negators? -- 2.5 Summary.
Description based on publisher supplied metadata and other sources
Keywords: Greek language-History; Electronic books; Hochschulschrift